The Chestry oak - Seredy, Kate. (Cynthiana, Kentucky : Purple House Press, 2015)
"As he watches his homeland of Hungary being taken over by Nazi Germany, young Prince Michael of Chestry strives to retain his identity and integrity during WWII"--
Originally published: New York : Viking Press, 1948.
Keywords: World War, 1939-1945 -- Hungary -- Juvenile fiction; World War, 1939-1945 -- Hungary -- Fiction; Princes -- Fiction; Family life -- Hungary -- Fiction; Conduct of life -- Fiction; Horses -- Fiction; Hungary -- History -- 1918-1945 -- Fiction